From the CEO perspective: critical competencies for effective performance - Troilo, Fernando (2022)
The principal aim of this research has been to identify the critical competencies required for effective performance in the position of CEO in subsidiaries of multinational companies from the perspective of the players themselves. Eleven critical skills have been identified; the most significant of them are communication and interpersonal relationships, using a qualitative approach consisting of interviews with thirty CEOs.